Characterization of flavonoid-protein interactions using fluorescence spectroscopy: Binding of pelargonidin to dairy proteins. (15th December 2016) - Arroyo-Maya, Izlia J.; Campos-Terán, José; Hernández-Arana, Andrés; McClements, David Julian
Highlights: Interaction of protein with pelargonidin leads to quenching of protein fluorescence. Quenching seemingly originates from a binding process. Pelargonidin binding does not affect protein secondary structure. Non-covalent forces underlying binding are inferred from thermodynamics parameters. Abstract: In this study, the interaction between the flavonoid pelargonidin and dairy proteins: β-lactoglobulin (β-LG), whey protein (WPI), and caseinate (CAS) was investigated. Fluorescence experiments demonstrated that pelargonidin quenched milk proteins fluorescence strongly. However, the protein secondary structure was not significantly affected by pelargonidin, as judged from far-UV circular dichroism. Analysis of fluorescence data indicated that pelargonidin-induced quenching does not arise from a dynamical mechanism, but instead is due to protein−ligand binding. Therefore, quenching data were analyzed using the model of independent binding sites. Both β-LG and CAS, but not WPI, showed hyperbolic binding isotherms indicating that these proteins firmly bound pelargonidin at both pH 7.0 and 3.0 (binding constants ca. 1.0 × 10 5 at 25.0 °C). To investigate the underlying thermodynamics, binding constants were determined at 25.0, 35.0, and 45.0 °C. These results pointed to binding processes that depend on the structural conformation of the milk proteins.